MANAJEMEN PENDIDIKAN BERBASIS NILAI ISLAM: STUDI PADA SEKOLAH DASAR KUTTAB IMAM SYAFI’I - Riswanto, Aji (Jurnal Manajemen Pendidikan Islam Al-Munadzomah, 2025)
This study examines the implementation of Islamic value-based management at SD Kuttab Imam Syafi'i, focusing on three main aspects: conceptualization, operationalization, findings reveal that the school successfully integrates national and Islamic curricula through a balanced approach (40% academic, 30% tahfizh, and 30% moral education). Key innovations include the adaptation of the classical talaqqi method into a modern, structured format and the consistent application of the principle "adab before knowledge" (adab sebelum ilmu). These strategies have significantly enhanced students' academic performance (85% achieved above-national KKM scores), moral discipline (90% parental-reported behavioral improvement), and practical worship skills. Challenges such as limited teacher expertise in multidisciplinary subjects, dense national curriculum demands, and scarce academic references on modern kuttab models were addressed through teacher training, curriculum adaptation, and documentation of best practices. The study contributes theoretically by enriching Islamic education management literature and empirically by demonstrating the effectiveness of holistic, value-based education. It recommends further longitudinal research, broader institutional adoption of the model, and government support for integrative Islamic curricula